Steps to Avoid Falls in the Elderly – a TECHnology Enhanced Intervention (SAFE-TECH) study: randomized controlled trial protocol for a community-based, multi-component fall prevention program - Wei Xuan Lai; Vanessa Koh; Jing Wen Goh; Kok Yang Tan; Kai Zhe Tan; Sai G. S. Pai; William R. Taylor; Abhijit Visaria; Navrag B. Singh; Angelique W. M. Chan; David B. Matchar (BMC Public Health)
Abstract Background Falls and fall-related injuries among older adults in Singapore are a serious health problem that require early intervention. In previous research, exercise interventions have been effective in improving functional outcomes and reducing falls for a broad group of older adults. However, results from multi-domain, multi-component falls prevention programs for high fall risk older adults in the community remain equivocal. One reason for these results is that there is significant heterogeneity in falls risk factors amongst high falls risk older adults which makes tailoring multicomponent interventions complex. The objective of the trial is to evaluate the effectiveness of an enhanced version of the predecessor program, SAFE. The Steps to Avoid Falls in the Elderly—a TECHnology enhanced intervention (SAFE-TECH) is designed for older adults in the community who are at high risk of falls, with candidate selection and program tailoring based on gait variables derived from wearable sensors and various questionnaire-based features. Methods SAFE-TECH is a 12-month randomized controlled trial involving 400 older adults at high risk of falling, who are randomly allocated to an intervention or control group in a 1:1 ratio. Participants will be assessed at baseline, 3rd-month and 12th-month for functional status, physical performance, cognitive status, quality of life, and medical history. Monthly phone calls will assess fall status, healthcare utilization, physical activity, and exercise self-efficacy. Participants in the intervention group will undergo a tailored, multi-domain, multi-component falls prevention program. The active intervention phase will last for 12-weeks with exercises focusing on strength, balance, coordination, flexibility, and aerobic endurance; and weekly educational sessions on falls risk with personalized feedback based on participant’s falls risk assessments and environmental checklist. Discussions SAFE-TECH seeks to evaluate enhanced existing falls prevention programs by addressing the heterogeneity of falls risk through rapid assessments and personalisation of exercise and education components while maintaining the efficiency of the group setting. Our findings will inform practical efforts to reduce falls and falls-related injuries among community-dwelling older adults. Trial registration ClinicalTrials.gov. Clinical Trial Number: NCT06102954|| 22–10-2023.